The Burden of Primary Caregivers of Spinal Muscular Atrophy Patients and Their Needs - (:unkn) unknown (AVES, 2021)
Aim: This study aims to reveal the problems faced by families of children with spinal muscular atrophy (SMA), by evaluating their care burden, needs, and expectations. Materials and Methods: The participants were the primary caregivers of 34 children between the ages of 0 and 18 years diagnosed with SMA. Thirteen children were diagnosed with type 1, 13 children with type 2 and 8 children with type 3 SMA. Data on the medical history, functional levels of the participants, and the characteristics of families were collected. The childrens' parents completed the Family Needs Survey and the Zarit Caregiver Burden Scale. Results: According to the results of the Family Needs Survey, it was found that information was the most common requirement, and this was independent of the level of education. According to the Caregiver Burden Scale, it was recorded that 64.7% of the caregivers were under mild/moderate burden. While there was a moderate correlation (r = 0.574; p < .001) between the Caregiver Burden Scale and the Family Needs Survey, it was observed that the functional level of the child was not associated with family needs and caregiver burden. Conclusions: Our study suggests that the needs of families of SMA patients, especially related to income level, have changed. The caregivers' burden is not directly related to the income level or the functional level of the child. Families' need for information should also be prioritized within the rehabilitation program.
Keywords: Care burden; family needs; social support; spinal muscular atrophy; QUALITY-OF-LIFE; CHILDREN; ADOLESCENTS; PARENTS; ANXIETY; STRESS